Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/children8080700
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress Symptoms and Resilience Assets in Adolescents in Residential Care

Abstract: Most studies with institutionalised children and adolescents focus on evaluating the impact of negative life events on emotional development. However, few have investigated the relationship between resilience assets and the teenagers’ psychopathological problems. The purpose of the present study was to investigate differences in psychological distress symptoms and in resilience assets in institutionalised and non-institutionalised adolescents. A total of 266 adolescents aged between 12 and 19 years old took pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…In the present study, the adolescents with psychosocial risk showed higher scores regarding the presence of negative life events, compared to the general group. These data are congruent with the literature, in which youth at psychosocial risk experience many more negative life events than youth not at risk, with more frequency and greater impact [26,41], as well as in the setting of negative life events associated with psychological and sexual abuse, and related to separations and losses, which are experienced more by youth in an adverse social environment than by youth free of psychosocial risk [38,42].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the present study, the adolescents with psychosocial risk showed higher scores regarding the presence of negative life events, compared to the general group. These data are congruent with the literature, in which youth at psychosocial risk experience many more negative life events than youth not at risk, with more frequency and greater impact [26,41], as well as in the setting of negative life events associated with psychological and sexual abuse, and related to separations and losses, which are experienced more by youth in an adverse social environment than by youth free of psychosocial risk [38,42].…”
Section: Discussionsupporting
confidence: 87%
“…The importance of this differentiation between the groups was due to previous studies indicating that the existence of greater psychosocial vulnerability may lead to greater suicidal ideation [38]. In this line of reasoning, young people from families at psychosocial risk are more likely to experience negative events in their environment and in the presence of psychological risk factors, which act as facilitators of suicidal ideation [21,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QoL cannot be attributed only to the absence of problems, but must incorporate degrees of positive experience, such as happiness, satisfaction, and meaning to reflect the full range of well-being [95], and PI is an unavoidable indicator of a child's well-being. Therefore, parents' involvement in their children's daily life routines and experiences can constitute a very protective factor for the children's QoL and well-being [93] and a preventive mechanism against ill-being [96,97].…”
Section: Discussionmentioning
confidence: 99%
“…In a very specific topic, children followed by child protective services, the contributions of Lemos et al [ 12 ], Pires et al [ 13 ], Salomão et al [ 14 ], and Stuart et al [ 15 ] present different orientations on how to intervene with these families in children at risk situations.…”
mentioning
confidence: 99%